Transforming Collaborative Service Specifications into Efficiently Executable State Machines - Kraemer, Frank Alexander; Herrmann, Peter (Electronic Communications of the EASST, 2007)
We describe an algorithm to transform UML 2.0 activities into state machines. The implementation of this algorithm is an integral part of our tool-supported engineering approach for the design of interactive services, in which we compose services from reusable building blocks. In contrast to traditional approaches, these building blocks are not only components, but also collaborations involving several participants. For the description of their behavior, we use UML 2.0 activities, which are convenient for composition. To generate code running on existing service execution platforms, however, we need a behavioral description for each individual component, for which we use a special form of UML 2.0 state machines. The algorithm presented here transforms the activities directly into state machines, so that the step from collaborative service specifications to efficiently executable code is completely automated. Each activity partition is transformed into a separate state machine that communicates with other state machines by means of signals, so that the system can easily be distributed. The algorithm creates a state machine by reachability analysis on the states modeled by a single activity partition. It is implemented in Java and works directly on an Eclipse UML2 repository.